EFFICACY OF GROUNDNUT SHELL AND TEA LEAVES WASTE ON ADSORPTION OF CHROMIUM AND ARSENIC IN WASTE WATER IN GOMBE METROPOLIS - Usman Y. M; Muzakir M.M; Stephen J. E; Mohammed A.B (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Heavy metals in water are the contaminants occurring from global industrialization and anthropogenic sources attributed to an inappropriate effluence disposal of the untreated wastewater form threats. Water pollutants can damage living organisms in the ecosystem. This study was aimed at using environmentally friendly permeable substance of groundnut shell and tea leaves (waste) in the removal of Cr and As heavy metals in contaminated water. which were determined from the Tumfure wastewater are above the permissible limits to reduce its menance. The sample adsorbents were characterized using AAS, SEM for concentrations, morphology and FTIR analysis that revealed the functional groups of alkohols, metabolites, aromatic and aliphatic hydrocarbons, also the result show effective Adsorption of Groundnut shell and Tea leaves Waste of range of 93 to 98 %. The metal ion concentrations analyzed was found to be; As = 27.26 mg/L and Cr =11.35 mg/L. An Adsorbent dose, contact time, effects of pH and temperature as thermodynamic parameters were studied in a batch which showed percentage removal for As and Cr ions in the water sample from Tumfure by the adsorbents showed 94.31% As and Cr = 95.95% with Groundnut shell whereas 96.55 % As = 98.09 % Cr with Tea leaves respectively. Batch adsorptions was also carried out on dosage which ranged from 0.2 - 1.0g, temperature which were varied at 250c - 600c C, contact time showed a range of 10 - 60 minutes and effect of pH were varied at 2 pH -10 pH respectively. The kinetic or adsorption process was tested to range between 0.04 t0 1 through pseudo first order and pseudo second order models. The Pseudo Second Order Kinetic Model provided the best correlation for experimental data for the two metals ions. Thermodynamics parameter, that’s ΔG0, ΔH0 and ΔS0 were also calculated which showed that the process of adsorption for ΔG0 were negative showing spontaneity.